Analisa Gameplay Metric pada Game “Survive Jok” menggunakan unity analytics - riwinoto riwinoto; Alfian Akmal (Politeknik Negeri Batam, 2021)
Gameplay Metrics are about measuring a player's habits in a game such as navigation, items, use of abilities, jumping, progress or whatever a player in a game is doing either 2D or 3D. one way to get data for Gameplay Metrics is to use an application that can calculate each interaction between the player and the game being played and can provide data in the form of interaction results for each specified variable. In this case, the author wants to use Unity Analytics in the Unity 3D application to get Gameplay Metrics results to be able to analyze Gameplay in the game. The game used is a game that was created by the author with the title